An essay on schooling outcomes in the Philippines the role of households, markets, and institutions - Revilla, Ma. Laarni D.; Estudillo, Jonna P. (The Philippine Review of Business and Economics, 2016)
This essay explores the impacts of household income, markets, and institutions on schooling outcomes of children in high school age in the Philippines. We found that the development of the labor market and the rise in household income have encouraged schooling investment. The implementation of free secondary school act (Republic Act 6655) in 1988 has exerted positive impacts on schooling outcomes by decreasing the direct cost of schooling borne by parents. This finding suggests that government policies that decrease user fees in school tend to encourage parents to send their children to school.